2003
DOI: 10.1021/es026292g
|View full text |Cite
|
Sign up to set email alerts
|

On Dioxin Formation in Iron Ore Sintering

Abstract: Iron ore sintering is an important source of "dioxins", polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs). This paper reports on attempts to identify materials, conditions, and mechanisms responsible for PCDD/F formation (i) by investigating salient properties of ores (viz., with respect to oxidation, condensation, and chlorination of model organics) and (ii) by mimicking the industrial process on a microscale with real-life materials. Principles of Design of Experiments (DOE) are employed. The rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 13 publications
4
27
0
Order By: Relevance
“…It might be because the involved raw materials for the iron ore sintering process, such as iron ore and return fines, were abundant in both K + , and Na + (Cieplik et al, 2003;Nakano et al, 2005). The above results were also comparable to that conducted by Tsai et al (2007).…”
Section: Ionic Constituents Containing In Wb Dustssupporting
confidence: 64%
See 1 more Smart Citation
“…It might be because the involved raw materials for the iron ore sintering process, such as iron ore and return fines, were abundant in both K + , and Na + (Cieplik et al, 2003;Nakano et al, 2005). The above results were also comparable to that conducted by Tsai et al (2007).…”
Section: Ionic Constituents Containing In Wb Dustssupporting
confidence: 64%
“…The de novo synthesis has been considered as an important formation pathway of PCDD/Fs during the iron ore sintering process according to the results obtained from several field and laboratory investigations (Kasai et al, 2001a(Kasai et al, , 2001bXhrouet et al, 2001;Cieplik et al, 2003;Kuzuhara et al, 2003;Suzuki et al, 2004;Kasama et al, 2006;Tsubouchi et al, 2006). For example, a series of laboratory sinter-pot studies have identified that the de novo synthesis could be occurred in the drying zone of the sinter bed (Cieplik et al, 2003). More recently, the concept of the two-stage release of PCDD/Fs from the rear half part of the sinter strand has been proposed by Kasama et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…There is also the presence of chlorine as alkali chlorides and small amounts of Cu in this region (Suzuki et al, 2004). The raw material can contain substances that have been reported to be essential or facilitate the formation of PCDD/Fs e.g., chlorine, organic compounds and metal catalysts like Cu (Cieplik et al, 2003). However, though the current understanding is that PCDD/F are majorly formed within the sinter bed, an analysis of the dust particles in wind boxes revealed that it contains significant amounts of Cl and unburnt carbon (Tsubouchi et al, 2006;Kuo et al, 2011) making it a potential area for PCDD/F formation.…”
Section: Pcdd/f Emissions From Sintering Plantsmentioning
confidence: 99%
“…Finally, this scenario was compared with the actual operation with regard to the emissions of dioxin (PCDD-Poly Chlorinated Di-benzene Dioxin) and furans(PCDF -Poly Chlorinated Di-benzene Furan). The sintering process have been strongly requested to reduce polychlorinated substances emissions, therefore, new technologies need to be compared not only from the point of view of economics but also from the environmental load (Castro et al 2005, Cieplik et al 2003, Kasai et al 2008. Figure 9 and 10 show the comparisons of PCDD and PCDF distributions within the sinter strand for actual operation and case 6.…”
Section: Simulations Of Advanced Operations Techniquesmentioning
confidence: 99%
“…The physicochemical and thermal phenomena involved in this process are complex and numerous ( Nakano et al, 2010, Kamijo et al 2009, Kasai et al 2008. Special mention is made to the phenomena of gas flow through the porous bed, gas-solid heat transfer, drying, vaporization and several chemical reactions and phase transformations (Umekage et al 2009, Cieplik, 2003, Cores et al 2010. Several attempts have been done to predict the final properties of the sinter product (Water et al 1989, Kasai et al 1989, 1991.…”
Section: Introductionmentioning
confidence: 99%